2018
DOI: 10.1503/cmaj.170691
|View full text |Cite
|
Sign up to set email alerts
|

Addressing overestimation of the prevalence of depression based on self-report screening questionnaires

Abstract: ental health disorders, including major depressive disorder, are classified in research using validated diagnostic interviews. 1,2 However, administering diagnostic interviews to large population samples to estimate prevalence is expensive because of the time and trained personnel that are required. This is likely why researchers increasingly use selfreport screening questionnaires, which require fewer resources, to estimate prevalence. We searched PubMed from Jan. 1, 2017, to Mar. 14, 2017, for primary studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
180
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(190 citation statements)
references
References 24 publications
7
180
2
1
Order By: Relevance
“…Another factor that may explain variation in rates of depressive symptoms is the measurement of symptoms, which includes the use of a clinical diagnostic interview to classify major depressive disorder versus self‐report screening questionnaires . Although screening questionnaires are often used because of their convenience (ie, inexpensive and quick to administer to large groups), it should be noted that screening questionnaires overestimate the prevalence of depression .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another factor that may explain variation in rates of depressive symptoms is the measurement of symptoms, which includes the use of a clinical diagnostic interview to classify major depressive disorder versus self‐report screening questionnaires . Although screening questionnaires are often used because of their convenience (ie, inexpensive and quick to administer to large groups), it should be noted that screening questionnaires overestimate the prevalence of depression .…”
Section: Discussionmentioning
confidence: 99%
“…26 Additionally, psychosocial support throughout the cancer trajectory has improved and cancer survi- Another factor that may explain variation in rates of depressive symptoms is the measurement of symptoms, which includes the use of a clinical diagnostic interview to classify major depressive disorder versus self-report screening questionnaires. 1,28 Although screening questionnaires are often used because of their convenience (ie, inexpensive and quick to administer to large groups), it should be noted that screening questionnaires overestimate the prevalence of depression. 28 In addition, variation in rates of depressive symptoms may not only be explained by using different screening instruments but also by using different cutoff thresholds within a distinct instrument for determining elevated depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilising a robust methodology, Mantry et al (2008) found that mental illness clinically affected 23.7% of adults with DS, but the prevalence would lower to 10.8% if applying Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition Revised criteria. The recent research corroborated that applying an inappropriate diagnostic method for depression exaggerated its prevalence at least twice that of the true prevalence (Thombs et al 2018). While depression, anxiety, obsessivecompulsive disorder and behavioural issues make up most diagnoses for mental illness in DS (Jensen & Bulova 2014), the prevalence of mental illness in DS adults was lower compared with other adults with IDs (Mantry et al 2008).…”
Section: Discharge Statusesmentioning
confidence: 73%
“…The recent research corroborated that applying an inappropriate diagnostic method for depression exaggerated its prevalence at least twice that of the true prevalence (Thombs et al . ). While depression, anxiety, obsessive–compulsive disorder and behavioural issues make up most diagnoses for mental illness in DS (Jensen & Bulova ), the prevalence of mental illness in DS adults was lower compared with other adults with IDs (Mantry et al .…”
Section: Discussionmentioning
confidence: 97%